Role of teachers in imparting education to higher secondary students through e-learning during COVID-19: A survey (LIS TODAY, 2025)
The rapid growth of Information and Communication Technology (ICT) has changed how  we live and work. In education, ICT has become essential, especially through e-learning. This  study examines the role of e-learning in higher secondary education during the COVID-19  pandemic, focusing on teachers’ perceptions, experiences, and practices. A survey was  conducted with 250 teachers, achieving an 86% response rate. Key findings highlight that  94.9% of respondents utilized e-learning platforms, primarily through Google Classroom  and WhatsApp. While a substantial proportion of students participated in online classes,  significant gaps in attendance were noted. Challenges such as slow internet speeds and  difficulties in accessing information were prevalent. The findings underscore the need for  improved infrastructure and training to enhance the effectiveness of e-learning.
Keywords: E-Learning; COVID-19; Higher Secondary Education; Digital Learning Platforms